Dr. Death [videorecording (DVD)] - Jackson, Joshua, 1978-; Gummer, Grace, 1986-; Robb, AnnaSophia, 1993-; Slater, Christian; Baldwin, Alec, 1958- (Universal Pictures Home Entertainment, 2022)
Based on the hit podcast from Wondery, Dr. Death tells the shocking true story of Dr. Christopher Duntsch, a seemingly bright, young neurosurgeon with a thriving medical practice. But all is not as it seems. When a growing number of Dr. Duntsch's defenseless patients end up permanently maimed or worse, two fellow physicians, neurosurgeons Robert Henderson and vascular surgeon Randall Kirby, attempt to stop him before he causes any more harm.